Preparation and characterization of electrostatically selfassembled perylene-diimide/polyelectrolyte composites - Everett, Thomas A. (Kansas State University, 2010)
This doctoral thesis covers the synthesis, preparation, and characterization of a series of four perylene diimide derivatives, and the nanofibrous composite materials formed by these perylene diimides when complexed with oppositely charged polyelectrolytes. The perylene diimides include a symmetric dication (TAPDI2+), a symmetric dianion (PDISO32-), and two singly charged asymmetric varieties (C11OPDI+ and C7OPDI+) that contain a hydrophilic head group and hydrophobic ether tail. For all studies presented in the following chapters, poly(acrylate) (PA-) or poly(diallyldimethylammonium) chloride (PDDA+) are used as the polyelectrolytes (PEs). The patterned deposition of sheer aligned, nanofibrous material within a fluidic device is conclusively demonstrated. Thin films of the nanofibrous composite are prepared from aqueous solutions of the semiconducting perylene diimides and oppositely charged polyelectrolyte precursors. By sequentially exposing a clean glass substrate to the cationic and anionic precursor solutions, a thin film of composite material is deposited in a layer-by-layer fashion. By utilizing electrostatic self-assembly (ESA) and layer-by-layer (LbL) procedures, precise control of film thickness and optical density are obtained. The effect of perylene diimide structure and charge on resultant composite film morphology is explored. Through spectroscopic and microscopic studies of bulk perylene diimide solutions and composite thin films, it was determined that the formation of these fibrous materials is dependent on the aggregation of the PDI within the precursor solutions. The molecular orientation of the perylene diimide within the composite nanofiber was determined to be perpendicular to the fiber long axis. For the special case of C7OPDI+/PA- composite, flow induced fiber alignment was observed for both dip coated and flow coated samples. The influence of solution flow profile, PE molecular weight (MW), and PDI structure on deposition efficiency, macroscopic and microscopic morphology, and the potential for nanofiber alignment are investigated. Film formation mechanisms involving two unique routes are also presented.
Keywords: Thin film; Self-assembly; Perylene Diimide; Polyelectrolytes; Chemistry, Analytical (0486)